ПІДГОТОВКА ВЧИТЕЛІВ ПОЧАТКОВОЇ ШКОЛИ ДО ФОРМУВАННЯ ТОЛЕРАНТНОСТІ В МОЛОДШИХ ШКОЛЯРІВ У ПОЗАУРОЧНІЙ ДІЯЛЬНОСТІ - Сухопара, Ірина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розкрито зміст підготовки вчителів початкової школи до формування толерантності в молодших школярів. Охарактеризовано зміст програми вчительських студій «Формування толерантності в молодших школярів», завданнями якої є: розкрити важливість толерантності як цінності; завдання, зміст, структуру формування толерантності в молодших школярів; розглянути особливості формування толерантності в учнів початкової школи; ознайомити педагогів початкової школи з діагностикою рівнів сформованості толерантності в учнів молодшого шкільного віку. В статье раскрыто содержание подготовки учителей начальной школы к формированию толерантности у младших школьников. Охарактеризованы содержание программы учительских студий «Формирование толерантности у младших школьников», задачами которой являются: раскрыть значение толерантности как ценности; задачи, содержание, структуру формирования толерантности у младших школьников; рассмотреть особенности формирования толерантности у учащихся начальной школы; ознакомить педагогов начальной школы с диагностикой уровней сформированности толерантности у учащихся младшего школьного возраста. The article considers some approaches to improving training of teacher of elementary school to tolerance formation of junior schoolchildren’s. We consider conten training of teacher. Tolerance of teacher– the component of active position of educator who have a system values and interests, readiness to protect them, at the same time to respect position and values of schoolchildren and other people, to interact with them with harmony and understanding. Characterized content of teachers studious «Tolerance formation of junior schoolchildren» goal of which is to uncover importance of tolerance as a system of values the task of them, content, structure of tolerance formation of junior schoolchildrens; to acquaint teachers of elementary school; to acquaint teachers of elementary school with the diagnostics tolerance formation levels ; to acquaint elementary school teachers with pedagogical conditions of tolerance formation of junior schoolchildrens in extracurricular activities.